Belize : Climate Change Policy Assessment. (IMF Staff Country Reports; Country Report, 2018)
Belize is exceptionally vulnerable to natural disasters and climate change. It already faces hurricanes, flooding, sea level rise, coastal erosion, coral bleaching, and droughts, with impacts likely to intensify given expected increases in weather volatility and sea temperature. Hence, planning for resilience-building, and engagement with development partners on environmental reforms, have been central to Belizean policymaking for many years, since well before Belize submitted its Nationally Determined Contribution (NDC) to the Paris Accord in 2015. This Climate Change Policy Assessment (CCPA) takes stock of Belize's plans to manage its climate response, from the perspective of their macroeconomic and fiscal implications. The CCPA is a joint initiative by the IMF and World Bank to assist small states to understand and manage the expected economic impact of climate change, while safeguarding long-run fiscal and external sustainability. It explores the possible impact of climate change and natural disasters on the macroeconomy and the cost of Belize's planned response. It suggests macroeconomically relevant reforms that could strengthen the likelihood of success of the national strategy and identifies policy gaps and resource needs.